Answer:
g = ![\frac{b+4+2h}{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bb%2B4%2B2h%7D%7B2%7D)
Step-by-step explanation:
Given
2(g - h) = b + 4 ← distribute parenthesis on left side
2g - 2h = b + 4 ( add 2h to both sides )
2g = b + 4 + 2h ( divide both sides by 2 )
g = ![\frac{b+4+2h}{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bb%2B4%2B2h%7D%7B2%7D)
Answer:
y-intercept: (0, 2.5)
x-intercept: (1.67, 0)
Step-by-step explanation:
Right now, you have 3x + 2y = 5. You want to change it into slope-intercept form to make the problem easier to solve.
2y = -3x + 5
y = -3/2x + 5/2
From here, you can see that the y-intercept is (0, 5/2). You can also say that the y-intercept is (0, 2.5).
To get the x-intercept, substitute 0 for y.
0 = -3/2x + 5/2
3/2x = 5/2
3x = 5
x = 5/3
So, the x-intercept is (5/3, 0). You can also say that the x-intercept is (1.67, 0).
Hope this helps!
Answer:
d =7.6
Step-by-step explanation:
![(-3,11) =(x_1,y_1)\\(-6,4)=(x_2,y_2)\\\\\mathrm{Compute\:the\:distance\:between\:}\left(x_1,\:y_1\right),\:\left(x_2,\:y_2\right):\\\quad \sqrt{\left(x_2-x_1\right)^2+\left(y_2-y_1\right)^2}\\\\=\sqrt{\left(-6-\left(-3\right)\right)^2+\left(4-11\right)^2}\\= \sqrt{(-6+3)^2+(4-11)^2}\\ \\d= \sqrt{(-3)^2+(-7)^2} \\\\d = \sqrt{9+49}\\ \\d = \sqrt{58}\\\\d = 7.61577\\\\d =7.6](https://tex.z-dn.net/?f=%28-3%2C11%29%20%3D%28x_1%2Cy_1%29%5C%5C%28-6%2C4%29%3D%28x_2%2Cy_2%29%5C%5C%5C%5C%5Cmathrm%7BCompute%5C%3Athe%5C%3Adistance%5C%3Abetween%5C%3A%7D%5Cleft%28x_1%2C%5C%3Ay_1%5Cright%29%2C%5C%3A%5Cleft%28x_2%2C%5C%3Ay_2%5Cright%29%3A%5C%5C%5Cquad%20%5Csqrt%7B%5Cleft%28x_2-x_1%5Cright%29%5E2%2B%5Cleft%28y_2-y_1%5Cright%29%5E2%7D%5C%5C%5C%5C%3D%5Csqrt%7B%5Cleft%28-6-%5Cleft%28-3%5Cright%29%5Cright%29%5E2%2B%5Cleft%284-11%5Cright%29%5E2%7D%5C%5C%3D%20%5Csqrt%7B%28-6%2B3%29%5E2%2B%284-11%29%5E2%7D%5C%5C%20%5C%5Cd%3D%20%5Csqrt%7B%28-3%29%5E2%2B%28-7%29%5E2%7D%20%5C%5C%5C%5Cd%20%3D%20%5Csqrt%7B9%2B49%7D%5C%5C%20%5C%5Cd%20%3D%20%5Csqrt%7B58%7D%5C%5C%5C%5Cd%20%3D%207.61577%5C%5C%5C%5Cd%20%3D7.6)
Answer:
x < -8
Step-by-step explanation:
-x - 10 > 14 + 2x
Subtract 2x from both sides;
-3x - 10 > 14
Add 10 to both sides;
-3x > 24
Divide both sides by -3
The sign switches when divide by a negative number.
x < -8